2020
DOI: 10.1039/c9na00643e
|View full text |Cite
|
Sign up to set email alerts
|

Shape- and size dependent piezoelectric properties of monolayer hexagonal boron nitride nanosheets

Abstract: A symmetry analysis of 2D BN nanosheet geometries is carried out. We demonstrate effective shape tuning of piezoelectric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…The piezoelectric properties of LD materials are mainly dependent on the layered atomic thickness film with a noncentrosymmetric structure. The layered material should also have a certain charge delocalization for the piezoelectric property. It is worthwhile mentioning that metals do not have piezoelectric properties because the high electron concentration shields the polarization charges.…”
Section: Principles and Performance Indicators For Piezoelectricitymentioning
confidence: 99%
“…The piezoelectric properties of LD materials are mainly dependent on the layered atomic thickness film with a noncentrosymmetric structure. The layered material should also have a certain charge delocalization for the piezoelectric property. It is worthwhile mentioning that metals do not have piezoelectric properties because the high electron concentration shields the polarization charges.…”
Section: Principles and Performance Indicators For Piezoelectricitymentioning
confidence: 99%
“…Due to their excellent physical properties, XNs have been shown to be promising in a variety of applications in recent years, including nanoelectronics, spintronics, optoelectronics, and heterojunction devices. The substantial difference in electronegativity between constituent elements in group III nitrides is expected to exhibit significant polarization on mechanical agitation. Nan et al investigated the piezoelectric characteristics of 2D h -BN nanosheets and found that the microscopic structure has a considerable effect on the piezoelectric behavior. A nanowire of InN may produce a piezoelectric potential of up to 1 V in a nanogenerator, and the direction of the transverse force affects the polarity of the potential .…”
Section: Introductionmentioning
confidence: 99%
“…Since the group-III nitrides are electronegative in nature, it is predicted that these materials will demonstrate significant polarization with external mechanical disposition 35 40 . To this extent, Nan et al 41 have investigated piezoelectricity in 2D hexagonal boron nitride nanosheets (BNNS) and posited that piezoelectricity in BNNS strongly depends on the microscopic shape of the structure. In a single layer InN nanowire nanogenerator, a piezoelectric potential as high as 1 V can be obtained, and the polarity of the potential depends on the direction of the applied transverse force 42 .…”
Section: Introductionmentioning
confidence: 99%